Resistance Trainings for Enhancement in Jumping Performance: A Comparative Analysis - Sana Ullah Khan; Muhammad Farhan Tabassum; Rabia Karim (The Sky, 2023)
The primary purpose of programming is to organize training factor modifications that will provide the greatest possible improvement in performance. However, the best programming approach that results in enhanced neuromuscular adaptations is still unclear. This research set out to determine how three varying degrees of unpredictability within resistance training programs affected performance gains. Thirty-six people were split into three groups of twelve each: those who would receive training based on a weekly model (WM), those who would receive instruction based on a daily model (DM), and those who would receive training based on a session model (SM); Six weeks of back squat sessions comprised the training intervention. All participants received the same total training load during the course of six-week intervention. We tested the individual's maximum dynamic strength (1RM) in the back-squat, countermovement jump (CMJ), and squat jump (SJ) both before and after the training intervention. Significant gains were observed across the board (p<0.05). The effect size (ES) of the session model in 1RM is just 0.29.  Effect sizes for the daily model and session model in SJ are both moderate, at 0.61 and 0.41 respectively. The impact size in the CMJ daily model is quite moderate (0.51), while it is very large (0.99) in the session model.  The results of this study show that changing the type of stimulus used in resistance training more often is a significant way to improve both strength and jumping ability at the same time.